A eirōneía no diálogo socrático Clitofonte - Martha Macedo Rezende (2019)
The Clitophon consists in a speech by the athenian politician in the homonymous dialogue. When addressing to Socrates, Clitophon questions the value of the philosopher’s exortative speeches concerning justice. Seeing that each art (téchnē) has its own function or work (érgon), Clitophon expects Socrates’ to answer but remains unanswered. Socrates is then criticized, but falls silent though, what leads some of the 19th century commentators to consider this dialogue as spurious or as a riddle. Initially, Clitophon is reprehended by Socrates, for someone has told him that Clitophon had censured Socrates' diatribes and praised the company of Thrasymachus (406a1-4). It follows that Clitophon takes the turn and replies to Socrates' accusation and explains that Socrates may have heard wrongly, for there are some things that he has criticized, but not all the things. Clitophon, thus, says that he would gladly offer his parrhēsía. In his parrhēsiastic speech Clitophon praises Socrates' protrepticous, not without irony (408c2-3) and after this he critcizes what followed Socrates' exortations (408c4, 408c9, 408d7). He says that Socrates does not explicitly say how to start the learning of justice (408e2-3) which, as an art, consists of its own work (409c1) and who should teach it, if it is teachable at all. These questions, raised by him, are not answered by Socrates neither by his companions and, as a consequence, he concludes, Socrates is useless and almost an impediment to achieve the completeness of virtue and happiness. This dissertation aims to offer an alternative analysis of the eirōneía ascribed to Socrates in the platonic dialogues while distinguishing this linguistic approach from the ironic Clitophon's speech by comparing two texts whose authors hold different views, namely, “Socratic Irony”, by Gregory Vlastos, and “The evolution of eirōneia in Classical Greek Texts: Why Socratic eirōneia is not Socratic Irony”, by Melissa Lane. We also intend to approach the practise of parrhēsía in the fourth century BCE Athens, besides the intent of a new translation to the brazilian portuguese from the greek text established by John Burnet (Platonis Opera, ed. Oxford University Press. 1903).